Photo- and thermo-chemical transformation of AgCl and Ag2S in environmental matrices and its implication. (January 2017) - Yin, Yongguang; Xu, Wei; Tan, Zhiqiang; Li, Yanbin; Wang, Weidong; Guo, Xiaoru; Yu, Sujuan; Liu, Jingfu; Jiang, Guibin
Abstract: AgCl and Ag2 S prevalently exist in the environment as minerals and/or the chlorination and sulfidation products of ionic silver and elemental silver nanoparticles (AgNPs). In this work, we investigated the chemical transformation of AgCl and Ag2 S under simulated sunlight (in water) and incineration (in sludge and simulated municipal solid waste, SMSW). In the presence of natural organic matter, AgCl in river water was observed to be transformed into AgNPs under simulated sunlight, while photo-reduction of Ag2 S could not take place under the same experimental conditions. During the course of incineration, pure Ag2 S was transformed into elemental silver while AgCl remained stable; however, both Ag2 S in sludge and AgCl in SMSW can be transformed to elemental silver under incineration, evident by the results of X-ray absorption spectroscopy and scanning electron microscopy measurements. Incineration temperature played an important role in the transformation of Ag2 S and AgCl into elemental silver. These results suggest that chemical transformations of Ag2 S and AgCl into elemental silver could be a possible source of naturally occurring or unintentionally produced AgNPs, affecting the fate, transport, bioavailability and toxicity of silver. Therefore, it is necessary to include the contributions of this transformation process when assessing the risk of ionic silver/AgNPs and the utilization and management of incineration residues. Graphical abstract: Chemical transformations of Ag2 S and AgCl into elemental silver could be a possible source of naturally occurring or unintentionally produced AgNPs. Highlights: Transformation of AgCl into AgNP under sunlight in the presence of organic matter. Transformation of AgCl/Ag2 S into ionic/elemental Ag under incineration. Transformation of Ag2 S and AgCl is a possible source of natural AgNP. Risk of ionic Ag/AgNP in utilization of incineration residues should be assessed.